1980
DOI: 10.1042/bj1880643
|View full text |Cite
|
Sign up to set email alerts
|

Deficient metabolic utilization of hydrogen peroxide in Trypanosoma cruzi

Abstract: The glutathione peroxidase-glutathione reductase system, an alternative pathway for metabolic utilization of H2O2 [Chance, Sies & Boveris (1979) Physiol. Rev. 59, 527-605], was investigated in Trypanosoma cruzi, an organism lacking catalase and deficient in peroxidase [Boveris & Stoppani (1977) Experientia 33, 1306-1308]. The presence of glutathione (4.9 +/- 0.7 nmol of reduced glutathione/10(8) cells) and NADPH-dependent glutathione reductase (5.3 +/- 0.4 munit/10(8) cells) was demonstrated in the cytosolic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
84
0
8

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(93 citation statements)
references
References 23 publications
(31 reference statements)
1
84
0
8
Order By: Relevance
“…These enzymes have been located in all oxy-radical-generating compartments in plants, with multiple isoforms identified (14). In T. cruzi, significant levels of ascorbate and its oxidized form, dehydroascorbate (DHA), have been detected and previous studies have identified a microsomal-associated ascorbate-dependent peroxidase activity (2,15,16). Here we show that T. cruzi expresses an unusual plant-like ascorbate-dependent hemoperoxidase whose activity is linked to the trypanothione system.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…These enzymes have been located in all oxy-radical-generating compartments in plants, with multiple isoforms identified (14). In T. cruzi, significant levels of ascorbate and its oxidized form, dehydroascorbate (DHA), have been detected and previous studies have identified a microsomal-associated ascorbate-dependent peroxidase activity (2,15,16). Here we show that T. cruzi expresses an unusual plant-like ascorbate-dependent hemoperoxidase whose activity is linked to the trypanothione system.…”
mentioning
confidence: 80%
“…In contrast to most eukaryotes, T. cruzi lacks catalase and selenium-dependent glutathione peroxidases, enzymes capable of rapidly metabolizing high levels of H 2 O 2 (2,4,5). Instead it has an array of enzyme-mediated mechanisms in which the trypanosomatid-specific thiol trypanothione (N 1 ,N 8 -bisglutathionylspermidine) plays a pivotal role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trypanosomes and leishmania are much more sensitive towards oxidative stress than their respective hosts which may be due to the lack of glutathione peroxidase and catalase (Boveris et al, 1980;Carnieri et al, 1993). In trypanosomatids glutathione reductase is replaced by trypanothione reductase (Fairlamb and Cerami, 1992;Schirmer et al, 1995).…”
mentioning
confidence: 99%
“…It has been shown that the parasite antioxidant systems are essential for parasite survival and establishment of the infection in the vertebrate host (4)(5)(6)(7). In contrast to most eukaryotes, T. cruzi lacks catalase and selenium-dependent glutathione peroxidases, which are enzymes capable of rapidly metabolizing high levels of H 2 O 2 (8,9). Instead, it expresses an array of complex enzyme-mediated mechanisms in which the trypanosomatid-specific thiol trypanothione ([T(SH) 2 ], N 1 ,N 8 -bisglutathionylspermidine) plays a central role in the funneling of reducing equivalents to the different peroxidase antioxidant systems (10).…”
mentioning
confidence: 99%